2022
DOI: 10.1021/acsearthspacechem.2c00109
|View full text |Cite
|
Sign up to set email alerts
|

Important Routes for Methanediol Formation by Formaldehyde Hydrolysis Catalyzed by Iodic Acid and for the Contribution to an Iodic Acid Sink by the Reaction of Formaldehyde with Iodic Acid Catalyzed by Atmospheric Water

Abstract: Methanediol formed by the hydrolysis of formaldehyde is an important intermediate in the formation of formic acid in the atmosphere. However, the formation of methanediol by the direct reaction of formaldehyde (HCHO) with water (H2O) is not feasible in the gas phase in the atmosphere due to the very high enthalpy of activation at 0 K for the HCHO + H2O reaction. Here, by using quantum chemical methods and reaction rate theory, we report a new mechanistic route for the iodic acid-catalyzed gas-phase hydrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
(165 reference statements)
0
5
0
Order By: Relevance
“…Thus, it is very difficult to determine whether HCHO + HNO 3 can occur more feasibly than HCHO + HCOOH, as the error bars are produced at the two different theoretical methods and their energy barriers are very close to each other. However, the energy barrier of HCHO + HNO 3 (8.80 kcal/mol) is much higher (at least 5 kcal/mol) than those of the HCHO + H 2 SO 4 reaction (3.5–6.1 kcal/mol) at the W2X//QCISD/cc-pV­(T + d)­Z level, the HCHO + OH reaction (−0.12 kcal/mol) at the CCSD­(T)/aug-cc-pVTZ level, the HCHO + HO 2 reaction (−1.03 kcal/mol) at the MW3X-L//CCSD­(T)-F12a/cc-pVTZ-F12 level, the HCHO + CH 2 OO reaction (−5.26 kcal/mol) at the W3X-L//CCSD­(T)-F12a/cc-pVTZ-F12 level, and the HCHO + HIO 3 reaction (2.96 kcal/mol) at the CCSD­(T)-F12a/def2-TZVPP//M06-2X/aug-cc-pVTZ-PP level . It is noted that these reactions mentioned above were carried out using different theoretical methods; this can cause some different error bars for different theoretical methods.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, it is very difficult to determine whether HCHO + HNO 3 can occur more feasibly than HCHO + HCOOH, as the error bars are produced at the two different theoretical methods and their energy barriers are very close to each other. However, the energy barrier of HCHO + HNO 3 (8.80 kcal/mol) is much higher (at least 5 kcal/mol) than those of the HCHO + H 2 SO 4 reaction (3.5–6.1 kcal/mol) at the W2X//QCISD/cc-pV­(T + d)­Z level, the HCHO + OH reaction (−0.12 kcal/mol) at the CCSD­(T)/aug-cc-pVTZ level, the HCHO + HO 2 reaction (−1.03 kcal/mol) at the MW3X-L//CCSD­(T)-F12a/cc-pVTZ-F12 level, the HCHO + CH 2 OO reaction (−5.26 kcal/mol) at the W3X-L//CCSD­(T)-F12a/cc-pVTZ-F12 level, and the HCHO + HIO 3 reaction (2.96 kcal/mol) at the CCSD­(T)-F12a/def2-TZVPP//M06-2X/aug-cc-pVTZ-PP level . It is noted that these reactions mentioned above were carried out using different theoretical methods; this can cause some different error bars for different theoretical methods.…”
Section: Resultsmentioning
confidence: 96%
“…51 Thus, it is very difficult to determine whether HCHO + HNO 3 can occur more feasibly than HCHO + HCOOH, as the error bars are produced at the two different theoretical methods and their 40 and the HCHO + HIO 3 reaction (2.96 kcal/mol) at the CCSD(T)-F12a/def2-TZVPP//M06-2X/aug-cc-pVTZ-PP level. 59 It is noted that these reactions mentioned above were carried out using different theoretical methods; this can cause some different error bars for different theoretical methods. However, we also note that the error bars of these theoretical methods could be 1−2 kcal/mol in the HCHO + HNO 3 /H 2 SO 4 /OH/HO 2 /CH 2 OO/HIO 3 reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CH 3 CHO + H 2 SO 4 … (CH 3 ) 2 NH reaction occurs in one elementary step as depicted in Figure 1, which is similar to the hydrolysis of acetaldehyde catalyzed by sulfuric acid, as well as the reaction of formaldehyde with sulfuric acid catalyzed by formic acid and others. 34,36,50,51,53,81,82,83 It can be seen that when the H 2 SO 4 … (CH 3 ) 2 NH complex and CH 3 CHO act as reactants, the reaction occurs via the formation of prereaction complexes and then undergoes a unimolecular isomerization through these corresponding transition states responsible for the formation of post-reaction complex. In the CH 3 CHO + H 2 SO 4 … (CH 3 ) 2 NH reaction, there is a concerted reaction mechanism that the hydrogen atom of the OH group in sulfuric acid is transferred to the oxygen atom of the carbonyl group in CH 3 CHO by the amino group in dimethylamine, and simultaneously the oxygen atom of the S=O group in sulfuric acid is added to the carbon atom in CH 3 CHO, where dimethylamine is acted as a catalyst; this leads to the formation of the most stable post-reaction complex (CP1), which is a nucleation precursor of secondary organic aerosols.…”
Section: The Ch 3 Cho + H 2 So 4 Reaction Catalyzed By (Ch 3 ) 2 Nhmentioning
confidence: 99%
“…In addition, the reactivity of CH 2 O with OH via the α-hydrogen abstraction is 1 order of magnitude higher than that of CH 3 OH with OH in the gas phase . Recent studies have also shown that gaseous CH 2 (OH) 2 exists in mixtures of water and CH 2 O vapors, and acids have been theoretically predicted to be capable of catalyzing the formation of CH 2 (OH) 2 in the gas phase. Thus, the reaction involving CH 2 O could be drastically different in the highly moist environment, since the CH 2 O could be hydrated in the form of CH 2 (OH) 2 , which is less reactive in aqueous solution, as discussed above. In addition, CH 3 OH retarded the decay of N 2 O 3 more than CH 2 (OH) 2 did.…”
Section: Conclusion and Environmental Implicationsmentioning
confidence: 99%